2023
DOI: 10.1097/rlu.0000000000004841
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT in a Case of Thoracic SMARCA4-Deficient Undifferentiated Tumor

Jia Guo,
Zhongjian Liao,
Qing Chen
et al.

Abstract: Thoracic SMARCA4-deficient undifferentiated tumor is a rare, newly recognized poorly differentiated tumor with poor prognosis. FDG PET/CT findings of thoracic SMARCA4-deficient undifferentiated tumor are rarely reported. We describe FDG PET/CT findings in a case of thoracic SMARCA4-deficient undifferentiated tumor. The tumor presented as a pleural mass, destroyed the adjacent ribs, and showed intense FDG uptake with SUVmax of 12.7. This case indicates that thoracic SMARCA4-deficient undifferentiated tumor shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previous studies have shown the usefulness of 18 F-FDG PET/CT in the evaluation of SMARCA4-dUT. 5,6 Recent studies have reported that 68 Ga-FAPI PET/CT may be useful for the diagnosis of SMARCA4-dUT and may even be more advantageous over 18 F-FDG for detecting metastatic lesions. 7,8 In this case, 68 Ga-FAPI-46 PET/CT detected the occult SMARCA4-dUT located in the left pulmonary hilum, which was not visualized by 18 F-FDG PET/CT.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the usefulness of 18 F-FDG PET/CT in the evaluation of SMARCA4-dUT. 5,6 Recent studies have reported that 68 Ga-FAPI PET/CT may be useful for the diagnosis of SMARCA4-dUT and may even be more advantageous over 18 F-FDG for detecting metastatic lesions. 7,8 In this case, 68 Ga-FAPI-46 PET/CT detected the occult SMARCA4-dUT located in the left pulmonary hilum, which was not visualized by 18 F-FDG PET/CT.…”
Section: Figurementioning
confidence: 99%
“…Due to the rapid growth of SMARCA4-dUT, early diagnosis and accurate staging are crucial for patient management. Previous studies have shown the usefulness of 18 F-FDG PET/CT in the evaluation of SMARCA4-dUT 5,6 . Recent studies have reported that 68 Ga-FAPI PET/CT may be useful for the diagnosis of SMARCA4-dUT and may even be more advantageous over 18 F-FDG for detecting metastatic lesions 7,8 .…”
mentioning
confidence: 99%